REKAYASA KONSTRUKSI PEMANFAATAN BERAT AIR SEBAGAI ENERGI POMPA - Setiyadi Setiyadi; Andi Indianto (Politeknik Negeri Jakarta, 2016)
ABSTRACT Innovation is a way to change existing condition and develop it to become a better condition, generally we do innovation to fix the existing condition to become a more valuable condition. With innovation we can get the newness of existing condition to become a condition that has its strength. In technology, innovation is required, innovation can be done by fixing one of the component or adding another system that will boost the performance of the existing system. One of the simple technology that already give benefits for society especially village society for acquiring sanitary water is hydraulic ram, this kind of pump is drived by part of the water that will be pumped, it makes this pump doesn’t need driving machine.For that, this experiment is meant to make innovation by engineering the construction that acquired from weight of water that accommodated in weight system, where at the tip of the arm is given bucket container that can be filled with water and then emptied, this condition will arise the cyclic swing movement and this movement can be used as the force emergence initator. Then we can use the emerge force to drive the hand pump.After we integrate the construction of driving system and pump, then we test it. From the test of this pump system we know that basicly, pump driving system that come from the water that accommodated in weight system has already functionate as we expected, but the driving system still need to be perfected. And as for the pump,basicly it has functionate well, in spite of there still must other repairement and perfection. Keywords: innovation pump, hydraulic ram,